Information needs of prospective students to New Zealand - Chuah, Joo Bee. (2009)
This is a study on the information needs of students who intend to further their education overseas and looks at the information factors which are used in the decision process. In this case, the research focuses on prospective students to New Zealand who visited the New Zealand Education Centre in Singapore, as well as the staff at the Centre.